1982
DOI: 10.1002/cm.970020404
|View full text |Cite
|
Sign up to set email alerts
|

In situ demonstration of actin in normal and injured ocular tissues using 7‐nitrobenz‐2‐oxa‐1,3‐diazole phallacidin

Abstract: The fluorescent derivative of the actin-binding toxin phallacidin, 7-nitrobenz-2-oxa-1,3 diazole phallacidin, has been used to cytologically demonstrate the presence of actin in lens epithelium, corneal endothelium, and retinal pigment epithelium. In these noninjured tissues, no stress fibers are observed and fluorescence is confined mainly to an area at or near the cell membrane, although some diffuse cytoplasmic staining can also be seen. However, following injury to either the lens epithelium or corneal end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 48 publications
(35 reference statements)
0
21
0
Order By: Relevance
“…17 Similar MF bundles have been observed in lens and retinal pigment epithelial cells and in corneal endothelial cells. 29 We have not seen DPBs in confluent cultures of porcine thoracic aortic smooth muscle cells. The DPBs are not artifacts created by the close contact of MF bundles of two adjacent cells since even after removal of a single cell from the EC confluent monolayer* 5 the DPB is still present along the cell border adjacent to the absent cell.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…17 Similar MF bundles have been observed in lens and retinal pigment epithelial cells and in corneal endothelial cells. 29 We have not seen DPBs in confluent cultures of porcine thoracic aortic smooth muscle cells. The DPBs are not artifacts created by the close contact of MF bundles of two adjacent cells since even after removal of a single cell from the EC confluent monolayer* 5 the DPB is still present along the cell border adjacent to the absent cell.…”
Section: Discussionmentioning
confidence: 59%
“…Central MF bundles were present in those ECs that appeared to be under hemodynamic stress. Central MF bundles were also observed in in vivo migrating corneal endothelial and lens epithelial cells following injury 29 and in in vivo regenerating rabbit aortic ECs. 13 Gabbiani et al 13 recently reported that, in vivo, actin-containing MF were present at the periphery of aortic rabbit ECs while central MF bundles were present in ECs at sites located below intercostal arteries.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Continuum description of stress-fibers within a cell Contractile stress-fibers comprising proteins such as -actinin, actin, myosin and tropomyosin and showing an alternating periodic arrangement similar to that seen in muscle sarcomeres have been observed in a range of cells including endothelial cells (De Bruyn and Cho 1974), retinal cells (Gordon et al 1982) and fibroblasts (Byers and Fujiwara 1982). We use these observations to describe the structure of stress-fibers with a view to developing a continuum model for their re-organization.…”
Section: 1mentioning
confidence: 99%
“…Many studies of cell behaviour on glass or plastic have examined changes in the cytoskeleton and the sites of adhesive interactions with the substratum. Prominent among these have been studies examining the role of focal contacts and the associated microfilament bundles (stress fibers) in cell adhesion and migration of cells [Dipasquale, 1975b;Gordon et al, 1982;Soranno and Bell, 1982;Woods and Couchman, 19881. Focal contacts are regions of strong adhesion between cells and their substrata, where the basal plasma membrane comes within 10-15 nm of the substratum (usually plastic or glass) giving a characteristic black image when viewed with surface reflection interference microscopy [Izzard and Lochner, 19761. They are normally found at the ends of linear microfilament bundles or stress fibers, which are prominent in well-spread cultured cells [Heath and Dunn, 19781.…”
Section: Introductionmentioning
confidence: 99%